Configuration management metrics : product lifecycle and engineering documentation control measurements - Watts, Frank B. (Elsevier/William Andrew, 2010)
Configuration Management (CM) has become a key strategy for successful manufacturing companies. Controlling the design documentation throughout its lifecycle and knowing what is in the product is imperative for quickly moving a new product to the marketplace, identifying and making necessary changes as fast as possible. CM is similarly important to efficient, high quality and low cost supply chain and production processes. It is also critical to maintenance, repair, retrofit, service parts provisioning as well as the elephant in the room - liability protection. Fast, accurate, efficient, documented, measured and well understood Configuration Management is also critical to profitability. Frank Watts' Configuration Management Metrics gets engineers and managers up and running with Configuration Management measurement, reporting and benchmarking strategies designed to deliver world-class manufacturing outcomes. About the Author Frank Watts is a consultant with nearly 50 years of industrial and consulting experience. He has founded his own company to specialize in Configuration Management. Mr. Watts has guided the development of the engineering change control process at many companies, making significant contributions to improve new product release processes, install MRP/ERP systems and new numbering systems, and help companies attain a single BOM database, and guide reengineering of the Configuration Management processes. He is author of three editions of the Engineering Documentation Control Handbook.